Efek Pencampuran Butanol dan Diethyl Ether (DEE) Pada Pertalite Terhadap Torsi, Daya dan Brake Spesific Fuel Consumpsion Mesin Bensin 160cc - Sanjaya, Firman Lukman; Usman, M. Khumaidi; Fatkhurrozak, Faqih; Syarifudin, Syarifudin; Hendrawan, Andre Budhi (P3M Politeknik Negeri Cilacap, 2023)
The increase in the volume of vehicles resulted in a crisis of fossil fuels so there is a need for alternative fuels to replace gasoline. Butanol and Diethyl Ether (DEE) are alternative fuels that can be added to gasoline. This is because the Octane Number and high O2 levels optimize combustion in the cylinder and increase torque and power and save fuel. This study compares the addition of butanol and DEE to gasoline on torque, power, and Brake Specific Fuel Consumption (BSFC). The study used a 160cc gasoline engine with a carburetor with engine speeds of 1000, 2000, and 3000 rpm. Variation of fuel mixture 5%, 10%, and 15% on gasoline. The results showed that the DEE15 mixture increased the highest torque by 28% at 3000 rpm compared to other fuel mixtures. Engine power also increases the highest by 28% when using a mixture of DEE15 compared to other fuels. Meanwhile, BSFC experienced the highest decrease of 19% when using the DEE15 mixture compared to other mixtures.